African Swine Fever Virus Uses Macropinocytosis to Enter Host Cells - Sánchez, Elena G. (Public Library of Science, 2012)
African swine fever (ASF) is caused by a large and highly pathogenic DNA virus, African swine fever virus (ASFV), which provokes severe economic losses and expansion threats. Presently, no specific protection or vaccine against ASF is available, despite the high hazard that the continued occurrence of the disease in sub-Saharan Africa, the recent outbreak in the Caucasus in 2007, and the potential dissemination to neighboring countries, represents. Although virus entry is a remarkable target for the development of protection tools, knowledge of the ASFV entry mechanism is still very limited. Whereas early studies have proposed that the virus enters cells through receptor-mediated endocytosis, the specific mechanism used by ASFV remains uncertain. Here we used the ASFV virulent isolate Ba71, adapted to grow in Vero cells (Ba71V), and the virulent strain E70 to demonstrate that entry and internalization of ASFV includes most of the features of macropinocytosis. By a combination of optical and electron microscopy, we show that the virus causes cytoplasm membrane perturbation, blebbing and ruffles. We have also found that internalization of the virions depends on actin reorganization, activity of Na(+)/H(+) exchangers, and signaling events typical of the macropinocytic mechanism of endocytosis. The entry of virus into cells appears to directly stimulate dextran uptake, actin polarization and EGFR, PI3K-Akt, Pak1 and Rac1 activation. Inhibition of these key regulators of macropinocytosis, as well as treatment with the drug EIPA, results in a considerable decrease in ASFV entry and infection. In conclusion, this study identifies for the first time the whole pathway for ASFV entry, including the key cellular factors required for the uptake of the virus and the cell signaling involved.